2019
DOI: 10.3390/ijms20071713
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Amines and Their Guanidine Analogues Modulate Activation and Desensitization of ASIC3

Abstract: Acid-sensing ion channel 3 (ASIC3) is an important member of the acid-sensing ion channels family, which is widely expressed in the peripheral nervous system and contributes to pain sensation. ASICs are targeted by various drugs and toxins. However, mechanisms and structural determinants of ligands’ action on ASIC3 are not completely understood. In the present work we studied ASIC3 modulation by a series of “hydrophobic monoamines” and their guanidine analogs, which were previously characterized to affect othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…For example, recent studies have shown that homomeric ASIC1a was modulated by the alkaloid daurisoline isolated from the Chinese herb Menispermum dauricum [ 53 ]. ASIC3 channels were also modulated by endogenous isoquinoline alkaloids through reverse steady-state desensitization [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have shown that homomeric ASIC1a was modulated by the alkaloid daurisoline isolated from the Chinese herb Menispermum dauricum [ 53 ]. ASIC3 channels were also modulated by endogenous isoquinoline alkaloids through reverse steady-state desensitization [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shteinikov and co-workers [18] report the results of the experimental study on the action of the hydrophobic amines and their guanidine analogs on activation and desensitization of acid-sensing ion channels (ASIC). The ASIC3 subtype, studied here, with the highest acid sensitivity is primarily expressed in nociceptive neurons and likely implicated in various types of chronic and inflammatory pain associated with tissue acidosis.…”
mentioning
confidence: 99%